Revisiting the techno-economic analysis process for building-mounted, grid-connected solar photovoltaic systems: Part one – Review. (July 2017) - Sommerfeldt, Nelson; Madani, Hatef
Abstract: The market for solar photovoltaic systems is growing rapidly into a mature industry, while at the same time policies which have spurred the growth (e.g. feed-in tariffs or net metering) are beginning to fade away. These policies made techno-economic studies relatively simple for engineers, analysts, and owners, however investing in a deregulated market requires more advanced tools than the traditional engineering economics which dominate the literature. The objective of part one in this paper is to catalogue and critique the range of methods and models relevant to techno-economic analysis for PV systems in the context of distributed, grid-connected buildings. This is accomplished by; developing a system modeling framework for prosumer PV investment analysis, reviewing relevant energy, economics, and finance literature to identify mathematical models which can be applied, and cataloging the use of the reviewed techniques in the relevant literature. Also included is a qualitative discussion of the benefits and practicality of the review techniques, where Monte Carlo analysis is highlighted as an exemplary method. This review is useful as a reference for analysts, researchers, and engineers developing PV integration solutions for building energy systems in a post early adopter PV market. Highlights: A framework describing the PV prosumer's techno-economic system is presented. Review of technical, economic, and risk models for distributed solar PV. Methods in published literature are catalogued and frequency of use is identified. Monte Carlo analysis is highlighted for improving analyses for prosumers.